1961
DOI: 10.1017/s0021859600024667
|View full text |Cite
|
Sign up to set email alerts
|

The availability of iron in certain grass, clover and herb species III. Burnet, chicory and narrow-leaved plantain

Abstract: 1. The availability of iron in three herb species has been investigated, using the rat as the experimental animal.2. Two procedures were employed, namely, the increase in blood haemoglobin concentration, and the gain in total grama of haemoglobin, by nutritionally anaemic rats.3. Inorganic iron, as ferric chloride, was shown to be significantly more available than the iron contained in the three herbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1967
1967
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…The results obtained from the herbage samples were broadly similar to those found with equivalent botanical species by Raven and Thompson (1959) and Thompson and Raven (1959). The recommended minimal daily dietary intake of iron (Ottet aL, 1989) is 50 mg/kg dry weight for pregnant mares and 40 mg/kg for other adult horses.…”
Section: Discussionsupporting
confidence: 76%
“…The results obtained from the herbage samples were broadly similar to those found with equivalent botanical species by Raven and Thompson (1959) and Thompson and Raven (1959). The recommended minimal daily dietary intake of iron (Ottet aL, 1989) is 50 mg/kg dry weight for pregnant mares and 40 mg/kg for other adult horses.…”
Section: Discussionsupporting
confidence: 76%
“…1953; Raven ve ark. 1960;Thompson, 1961, Rojas ve ark. 1965Tilay ve France, 1990) yem sa ğlamaktad ı r. Bitki kök bo ğaz ı ndan fazlaca dallan ı p, toprak yüzeyini çok iyi kapatt ığı ndan, hem otlatmaya dayanmakta hem de çok iyi toprak koruma ve erozyon kontrolü sa ğlamaktad ı r (Valassis, 1957;Douglas ve ark.…”
Section: Giri şunclassified
“…It has been observed that calves reared in confinement and relying on milk only frequently experience iron deficiency. However, various iron sources include forages, oilseed meals, cereal grains, soil, and water ingestion [9,10]. It has been noticed that forage iron content varies considerably, and Fe bioavailability in animals from forages is markedly lower as compared to that from supplemental sources [11,12].…”
Section: Introductionmentioning
confidence: 99%